Key Factors For Successful Flood Disaster Knowledge Transfer In Riverbank Areas: A Literature Review - Rifanti, Dinda Putri; Permatasari, Karina Putri; Siswahyuni, Zulaika (Tarqabin Nusantara Group, 2024)
Introduction: Floods are seasonal disasters when water capacity overflows from existing waves and drowns the surrounding land. The losses incurred by floods, especially indirect losses, rank first or second after earthquakes or tsunamis. Methods: A systematic search of Cochrane, Google Scholar, PubMed, Scopus, Embase and Web of Science database reviews. The following keywords were used to conduct the literature search: